2009
DOI: 10.1007/s11802-009-0155-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination mechanisms in fish

Abstract: In fish, sex determination (SD) system shows high variation. The SD mechanisms include environmental and genetic regulation. The research on SD system and related genes in intensively studied fish species was reviewed. Although some genes have been described as sex-related, only DMRT1bY can be considered as a master sex determination gene and none of them has been utilized in aquaculture. The variation of fish SD system, the importance of sex-related genes in evolution research and the relations between enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Owing to the high proportion of pseudo-males in the C. semilaevis population and the necessity for sex control, it is of great significance to distinguish pseudo-males from males and females. To address this, the C. semilaevis genome laid a solid basis for understanding sex-determination mechanisms and developing sex identification methods 1 , 8 . On one hand, numerous genes related to sex determination and/or differentiation have been found, including DMRT1 1 , 9 , 10 , Dazl 11 13 , piwil2 14 , Figla 15 , GATA4 16 , aqp1aa 17 , and β-catenin1 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high proportion of pseudo-males in the C. semilaevis population and the necessity for sex control, it is of great significance to distinguish pseudo-males from males and females. To address this, the C. semilaevis genome laid a solid basis for understanding sex-determination mechanisms and developing sex identification methods 1 , 8 . On one hand, numerous genes related to sex determination and/or differentiation have been found, including DMRT1 1 , 9 , 10 , Dazl 11 13 , piwil2 14 , Figla 15 , GATA4 16 , aqp1aa 17 , and β-catenin1 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that Rb 1 attenuated ␤ AP 25-35 -induced tau protein hyperphosphorylation in cortical neurons, showed a possibility of inhibiting amyloid fibril formation by A␤. The research progress of ginsenoside Rg 1 , involved in the pharmacology of central nervous system, cardiovascular system, endocrine system, and immune system, revealed that Rg1 has the effect on Parkinson's disease and Alzheimer's disease, which were associated to A ␤ aggregation process [24].…”
Section: Introductionmentioning
confidence: 99%
“…The sex chromosomes are often not differentiated morphologically and often resist identification by chromosome staining techniques. In such cases, the sex chromosome system needs to be inferred from sex-reversal or other genomic manipulations [Ward, 2002;Zhang et al, 2009].…”
mentioning
confidence: 99%